ChemInform Abstract: Asymmetric Catalysis with CO2: The Direct α‐Allylation of Ketones. Issue 38 (September 2016) - Pupo, Gabriele; Properzi, Roberta; List, Benjamin
Abstract: For the first time, a direct and highly enantioselective Tsuji—Trost allylation of branched ketones is developed.